(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The aim of this study is to evaluate the effectiveness of risk management in Syrian banking with Basel standards using a model, The model argues eight factors as a key component of enterprise risk management effectiveness using coso framework and Basel standards. Data were obtained using questionnaire developed according to coso framework and Basel standards. 90 questionnaire distributed to employees who are working in the risk management department in Syrian banking ,26 acceptable responses were received. data has analyzed using spss. The findings from this paper conclude that there are all of the components (internal environment, objective setting , risk assessment, information and communication, monitoring ) in banking, and no there the components(event identification, risk response, control activities) in banking. يهدف البحث إلى تقييم فعالية إدارة المخاطر في البيئة المصرفية السورية وفق معايير بازل من خلال نموذج مقترح لتقييم الفعالية. تضمن النموذج ثمانية عوامل(متغيرات مستقلة) تعتبر المكونات الأساسية لإدارة مخاطر المنظمة وفق معايير بازل وإطار لجنة COSO . اعتمدت الدراسة على استراتيجية المسح في جمع البيانات وذلك عن طريق استخدام استبانة كأداة لجمع البيانات تم إعدادها بناءً على معايير بازل وإطار coso لإدارة المخاطر, تم توزيع 90 استبانه على موظفي إدارة المخاطر في المصارف في المصارف السورية, استرد منها 26 استبانة صالحة للتحليل. وقد تم تحليل البيانات بالاعتماد على برنامج SPSS . وقد خلصت النتائج التي توصل إليها البحث بالاعتماد على ىرنامج التحليل الإحصائي إلى أنه يوجد كل من المكونات التالية( بيئة الرقابة, تحديد الأهداف, تقييم المخاطر, المعلومات والاتصالات, المراقبة الدائمة) في المصارف المدروسة. بينما لايوجد كل من المكونات التالية(تمييز الحدث, استجابة المخاطر, أنشطة الرقابة) في المصارف المدروسة.